Diagnosis and management of severe combined immunodeficiency in Australia and New Zealand. (24th October 2020) - Richards, Stephanie; Gennery, Andrew R; Davies, E Graham; Wong, Melanie; Shaw, Peter J; Peake, Jane; Fraser, Chris; Gray, Paul; Brothers, Shannon; Sinclair, Jan; Prestidge, Tim; Preece, Kahn; et al.
Abstract : This consensus document outlines the recommendations from the Australasian Society of Clinical Immunology and Allergy Transplantation and Primary Immunodeficiency group for the diagnosis and management of patients with severe combined immunodeficiency. It also provides a proposed framework for the early investigation, management and supportive care prior to haematopoietic stem cell transplantation.